The Relationship between APGAR Family Score and Sleep Quality with Hypertension Observasional Study : A Cross-Sectional Study - Salsabila, Naura; Romadhon, Yusuf Alam (Universitas Muhammadiyah Surakarta, 2022)
Purpose : Indonesia is the 5th country with the highest prevalence 34,11% from the population. Based on the health center report in 2020 cases of hypertension at sukoharjo, there were 110,116 cases (69.18%) consisting of 49,510 men, 60,606 women. Meanwhile, at the Gatak Health Center there were 8,041 people who experienced hypertension which were divided into two, namely, 2,932 men and 5,109 women. Methode : To analyze the relationship APGAR Family Score and Sleep Quality with Hypertension. Observational analytic research with cross-sectional research design on primary data. The research sample is elderly 40 - >60 years. The sampling technique used cluster random sampling with a total sample of 86 elderly. Results : showed of the sample with elderly aged 40 - > 60 years old, male sex as many as 13 (18.6%), female sex as many as 57 (81.4%), dysfunctional family as much as 14 (20.0%), poor sleep quality as much as 66 (94.3 %). The results of the fisher test showed that there was a relationship between poor sleep quality and the incidence of hypertension with p 0.023 <0.05, but there is no relationship between APGAR family score and the incidence of hypertension with p 0.720 > 0.05. Value : Conclusion there is a relationship between poor sleep quality with hypertension, but there is no significant relationship between APGAR family score with hypertension.